Menganalisis Deret Konsonan Fonologi Bahasa Indonesia - Ulfiatussalwa Ulfiatussalwa; Syifa Nur Rohman; Tia Latifah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to analyze consonant sequences in the phonology of the Indonesian language, focusing on patterns of distribution, combinations, and variations of consonants. The analytical method involves collecting data from representative Indonesian language texts, including books, articles, and everyday conversations. The analysis is conducted by examining the sequence of consonants, frequency of usage, and potential phonological changes. The results of this research can provide further insights into the phonological structure of the Indonesian language, the contribution of consonant patterns to language expression, and their potential implications for language learning and teaching. This study is expected to contribute to a deeper understanding of Indonesian phonology and to encourage further development in the field of linguistics.